2014
DOI: 10.1371/journal.pone.0094946
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Structure of the Tick-Borne Encephalitis Virus Strains and Their Pathogenic Properties

Abstract: Tick-borne encephalitis virus (TBEV) is transmitted to vertebrates by taiga or forest ticks through bites, inducing disease of variable severity. The reasons underlying these differences in the severity of the disease are unknown. In order to identify genetic factors affecting the pathogenicity of virus strains, we have sequenced and compared the complete genomes of 34 Far-Eastern subtype (FE) TBEV strains isolated from patients with different disease severity (Primorye, the Russian Far East). We analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 92 publications
1
46
0
23
Order By: Relevance
“…This study continued the authors' experimental research of the biological and molecular genetic features of TBEV strains, isolated from people with various forms of disease in the Russian Far East (6,(24)(25)(26)40). This research in animal models, mostly mice, has shown that pathogenic potential (virulence) of the strains isolated from patients with inapparent infection was significantly lower compared to the strains causing severe focal TBE (6,25).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…This study continued the authors' experimental research of the biological and molecular genetic features of TBEV strains, isolated from people with various forms of disease in the Russian Far East (6,(24)(25)(26)40). This research in animal models, mostly mice, has shown that pathogenic potential (virulence) of the strains isolated from patients with inapparent infection was significantly lower compared to the strains causing severe focal TBE (6,25).…”
Section: Discussionmentioning
confidence: 52%
“…This research in animal models, mostly mice, has shown that pathogenic potential (virulence) of the strains isolated from patients with inapparent infection was significantly lower compared to the strains causing severe focal TBE (6,25). In cell culture models (PK cells and culture of human peripheral blood mononuclear cells), it has been found that TBEV strains differ in their replicative activity: nonpathogenic strains have lower rates of penetration and replication of viral particles in cells than pathogenic strains (20,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mice showed a strong cytokine response in periphery, low and delayed neuroinvasiveness, and low neurovirulence that, when translated into humans, might explain the lack of neurologic symptoms. Because genetic changes in TBEV could affect pathogenicity ( 12 , 13 ), future molecular studies are needed to determine the low pathogenicity of and enhanced immune response against low-virulence strain HB171/11.…”
Section: Discussionmentioning
confidence: 99%